Bone marrow mesenchymal stem cellsderived exosomes stabilize atherosclerosis through inhibiting pyroptosis - Zhibin Bai; Haolin Hu; Fangfang Hu; Jiajie Ji; Zhenling Ji (BMC Cardiovascular Disorders, 2023)
Abstract Objectives This study aimed to determine the effects of bone marrow mesenchymal stem cells (BMSCs)-derived exosomes (BMSC-EXO) on atherosclerosis (AS), and its related underlying mechanisms. Methods Exosomes were isolated from mouse BMSCs, and identified by transmission electron microscopy (TEM), Nanosight (NTA), and western blot. A mouse AS model was established, and exosomes were injected into the tail vein. Total cholesterol (TC) and triglycerides (TG) were detected using their corresponding assay kits. The contents of IL-1β and IL-18 in serum were detected by ELISA. The mRNA and protein expression levels of GSDMD, Caspase1, and NLRP3 were detected by qRT-PCR and Western blot. Finally, aortic tissues in the Model and BMSC-EXO groups were sent for sequencing. Results TEM, NTA, and western blot indicated successful isolation of exosomes. Compared with the control group, the TC, TG contents, IL-1β and IL-18 concentrations of the mice in the Model group were significantly increased; nonetheless, were significantly lower after injected with BMSC-EXO than those in the Model group (p < 0.05). Compared with the control group, the expressions of NLRP3, caspase-1 and GSDMD were significantly up-regulated in the Model group (p < 0.05), while the expressions of NLRP3, caspase-1, and GSDMD were significantly down-regulated by BMSC-EXO. By sequencing, a total of 3852 DEGs were identified between the Model and BMSC-EXO group and were significantly enriched in various biological processes and pathways related to mitochondrial function, metabolism, inflammation, and immune response. Conclusion AS can induce pyroptosis, and BMSC-EXO can reduce inflammation and alleviate the progression of AS by inhibiting NLRP3/Caspase-1/GSDMD in the pyroptosis pathway.